Design optimisation of perforated solar façades in order to balance daylighting with thermal performance. (15th November 2017) - Chi, Doris A.; Moreno, David; Navarro, Jaime
Abstract: On fully-glazed building façades perforated solar screens (PSS) are often used as an outer skin in order to reduce energy consumption and to solve issues such as visual appearance. However, not only must PSS control solar radiation but they must also provide adequate daylight levels, thus requiring a balanced solution. Currently, daylighting simulation software enables us to perform efficient daylight analysis of spaces with PSS. Notwithstanding this, current energy simulation software such as EnergyPlus cannot deal well with such geometry directly, making the thermal evaluation of PSS an infeasible task. This paper presents a methodology for achieving an integrated analysis of daylighting and energy consumption of spaces with PSS during the design stage. Such methodology provides daylight analysis through DIVA, and thermal analysis through EnergyPlus via DIVA/Grasshopper/Archsim. The aim is to optimise the dual performance of a balanced PSS solution through controlling its perforation percentage, matrix and shape, by using the orthogonal arrays (DOA) statistical method. DOA method is efficient in reducing the number of simulations derived from the combination of the aforementioned variables, and in identifying the optimal PSS configuration. In comparison to a non-optimised façade located in Seville, Spain, the predicted optimal PSS achieved a 50% increase in the actual daylit area and a 55% reduction in the total energy demand. Highlights: Integrated analysis of daylighting and energy consumption for perforated screens. Taking advantage of RADIANCE's capabilities of simulating complex geometries. Limiting the EnergyPlus' drawbacks on complex geometries energy calculations. Workflow to integrate the daylight, solar irradiation, and energy simulations. Use of orthogonal arrays to reduce the number of simulations performed.